Light Metals 2017 - Ratvik, Arne P. (The Minerals, Metals & Materials Series, 2017)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2017 collection includes papers from the following symposia: Alumina and Bauxite Aluminum Alloys, Processing, and Characterization Aluminum Reduction Technology Cast Shop Technology Cast Shop Technology: Recycling and Sustainability Joint Session Electrode Technology The Science of Melt Refining: An LMD Symposium in Honor of Christian Simensen and Thorvald Abel Engh.